2022
DOI: 10.3390/biomedicines10030704
|View full text |Cite
|
Sign up to set email alerts
|

CD5 Deficiency Alters Helper T Cell Metabolic Function and Shifts the Systemic Metabolome

Abstract: Metabolic function plays a key role in immune cell activation, destruction of foreign pathogens, and memory cell generation. As T cells are activated, their metabolic profile is significantly changed due to signaling cascades mediated by the T cell receptor (TCR) and co-receptors found on their surface. CD5 is a T cell co-receptor that regulates thymocyte selection and peripheral T cell activation. The removal of CD5 enhances T cell activation and proliferation, but how this is accomplished is not well underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Among them, N -Acetylornithine is a key intermediate metabolite in the biosynthesis pathway of arginine 60 . The regulation of metabolic pathways for alanine, glutamine, glutamate, arginine, and proline is facilitated through the participation of l -Aspartic acid 61 , 62 . Arginine participates in hormone secretion and immune regulation 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Among them, N -Acetylornithine is a key intermediate metabolite in the biosynthesis pathway of arginine 60 . The regulation of metabolic pathways for alanine, glutamine, glutamate, arginine, and proline is facilitated through the participation of l -Aspartic acid 61 , 62 . Arginine participates in hormone secretion and immune regulation 63 .…”
Section: Discussionmentioning
confidence: 99%
“…SRCR domains are divided into Group A and Group B based on the number and position of conserved cysteine residues [16,17], with Group A having six cysteine residues that form three pairs of disulfide bonds, and Group B having eight cysteine residues that form four pairs of disulfide bonds [18]. For instance, CD5 (cluster of differentiation 5) [19], CD6 (cluster of differentiation 6) [20], and DMBT1 (deleted in malignant brain tumor 1) [21] belong to Group B, whereas MARCO (macrophage receptor with collagenous structure) [22], Mac2BP (Mac-2 binding protein) [23], and LOX (lysyl oxidase) family (LOX-like 2, LOX-like 3, and LOX-like 4) [24] belong to Group A. Until now, research on SRCR-SFs within Group B has primarily focused on vertebrates, with only one reported instance in the invertebrate Geodia cydonium [25].…”
Section: Introductionmentioning
confidence: 99%